Intermediate type of Juvenile Paget's disease: A rare case in Indian population - S Ravi Raja Kumar; Bhavana S Bagalad; Ch. Balakrishna Manohar; Puneeth H Kuberappa (Wolters Kluwer Medknow Publications, 2017)
Juvenile Paget's disease (JPD), a rare genetic skeletal disorder characterized by accelerated bone turnover with elevated levels of serum alkaline phosphatase, presents in early childhood. We report a female patient with typical features of JPD with dental finding who remained undiagnosed until 18 years of age. Scarcity of this disease in the Indian literature and need for timely diagnosis to avert progression of disease thus incited us to report this case.